2010
DOI: 10.1105/tpc.109.071662
|View full text |Cite
|
Sign up to set email alerts
|

Endosome-Associated CRT1 Functions Early in Resistance Gene–Mediated Defense Signaling in Arabidopsis and Tobacco

Abstract: Resistance gene–mediated immunity confers protection against pathogen infection in a wide range of plants. A genetic screen for Arabidopsis thaliana mutants compromised for recognition of turnip crinkle virus previously identified CRT1, a member of the GHKL ATPase/kinase superfamily. Here, we demonstrate that CRT1 interacts with various resistance proteins from different structural classes, and this interaction is disrupted when these resistance proteins are activated. The Arabidopsis mutant crt1-2 crh1-1, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 113 publications
(141 reference statements)
4
75
1
Order By: Relevance
“…We next tested interaction of HRT with CIB1 and COP1 proteins, because both CIB1 and COP1 are known to interact with CRY2 (12,36). Consistent with earlier results (38), CRY2 interacted with COP1 in the nucleus (Fig. 4A).…”
Section: Mutation In Blue-light Photoreceptors Compromises Hrt-mediatedsupporting
confidence: 66%
“…We next tested interaction of HRT with CIB1 and COP1 proteins, because both CIB1 and COP1 are known to interact with CRY2 (12,36). Consistent with earlier results (38), CRY2 interacted with COP1 in the nucleus (Fig. 4A).…”
Section: Mutation In Blue-light Photoreceptors Compromises Hrt-mediatedsupporting
confidence: 66%
“…CRT1 was subsequently shown to physically interact with HRT and ten other R proteins representing three different structural classes. This interaction appears to be dynamic as CRT1 bound inactive R proteins, but only poorly interacted with activated R proteins 13 . Analysis of the Arabidopsis genome revealed that CRT1 has two close (Z70% a.a. identity) and four distant (r50% a.a. identity) homologues.…”
mentioning
confidence: 99%
“…Cell death triggered by the R proteins ssi4 and RPS2 also was compromised by the crt1-1 mutation or silencing of CRT1 family members. Moreover, a double knockout (dKO) in the Col-0 background, crt1-2 crh1-1, which lacks CRT1 and its closest homologue, displayed compromised resistance to avirulent Pseudomonas syringae (Pst) and Hyaloperonospora arabidopsidis 13,14 . Construction of a triple KO was not possible as the CRH2 KO was lethal in the homozygous state.…”
mentioning
confidence: 99%
“…1073/pnas.1406611111/-/DCSupplemental. CRH6; Defective in Meristem Silencing 11 (DMS11)], and AtMORC7 (NP_194227; AT4G24970; CRH3) (25,(29)(30)(31)(32). AtMORC1 and AtMORC2 are the most closely related homologs and share 80.9% amino acid sequence identity (29)(30)(31)(32) (Fig.…”
Section: Significancementioning
confidence: 99%
“…AtMORC6 has been identified in four independent forward genetic screens (24)(25)(26)31) as required for gene silencing and maintenance of heterochromatin integrity. AtMORC1 is also required for gene silencing (26), although it was originally described as a master regulator in plant disease resistance signaling (30)(31)(32)(33).…”
Section: Significancementioning
confidence: 99%